Finite element study of adhesive bonded specimen with cracks - Lui, Wai Meng. (2009)
Mode I stress intensity factor of a center cracked adhesive bonded specimen has been analysed using finite element analysis which incorporates isoparameteric quarter-point elements at the crack tip.